BENTUK-BENTUK WADAH PENGUBURAN DALAM SISTEM KEPERCAYAAN MASYARAKAT MAMASA, SULAWESI BARAT - Bernadeta AKW (WalennaE, 2009)
Mamasa is one of the districts in West Sulawesi that many store various forms of culture and tradition which is still maintained. Cultural forms such as traditional houses and other burial containers and ancestral traditions that run in the context of belief systems. Survey indicates there are several types of burial containers in Mamasa "tedong-tedong" namely the tomb of the wooden containers mimic the anatomy of the buffalo, "Bangka-bangka" and "batutu" the tomb container placed on a home-like shape Mamasa traditional house. There are many similarities with both forms of the Toraja traditional houses and tradition run. This equation implies a close relationship between the two communities area. Mamasa adalah salah satu kabupaten di Sulawesi Barat yang banyak menyimpan berbagai bentuk budaya dan tradisi yang masih dipertahankan. Bentuk budaya seperti rumah tradisional dan wadah penguburan lainnya serta tradisi leluhur yang dijalankan dalam konteks sistem kepercayaan. Survei menunjukkan ada beberapa jenis wadah penguburan di Mamasa "tedong-tedong" yaitu makam dari wadah kayu meniru anatomi kerbau, "Bangka-bangka" dan "batutu" wadah makam yang diletakkan di rumah Mamasa seperti bentuk rumah tradisional. Ada banyak kesamaan dengan kedua bentuk rumah tradisional Toraja dan tradisi yang dijalankan. Persamaan ini menyiratkan hubungan yang erat antara wilayah dua komunitas.